Personality Traits and Vitamin D3 Supplementation Affect Mood State 12 h Before 100 km Ultramarathon Run - Krokosz, Daniel; Lipowski, Mariusz; Aschenbrenner, Piotr; Ratkowski, Wojciech (Frontiers in Psychology, 2018)
Background: Participation in extreme endurance sports is becoming an increasingly popular activity, and thus more and more people are getting involved in it. Taking part in a 100 km run is associated with great physiological and psychological stress, which can affect one’s mood state. Thus, the goal of this study was to determine if personality, experience, and motives for participation are related to a runner’s mood and its changes as well as to investigate whether vitamin D3 supplementation influences mood 12 hours before and 12 hours after the run. Method: The study group consisted of 20 experienced marathon and ultramarathon runners taking part in a 100 km track run. All participants were males aged between 31 and 50 (M = 40.75, SD = 7.15). The group was divided in two equal subgroups: the placebo group and the group supplemented with vitamin D3. Personality traits were assessed using the Polish version of Eysenck’s EPQ-R 106 and mood states were measured twice (12 hours before and after the run) using the Polish version of the UMACL by Mathews, Chamberlain, and Jones. Motives for participation in ultramarathons were measured with the IPAO by Lipowski and Zaleski. Results: Levels of vitamin D3 correlated very strongly with energetic arousal (rs = 0.80; p < 0.05) and strongly hedonic tone (rs = 0.74; p < 0.05) 12 hours before the run. There were no significant correlations between levels of vitamin D3 and mood states after the run. Moreover, extraversion correlated moderately with tense arousal (rs = -0.48; p < 0.05) and energetic arousal (rs = 0.47; p < 0.05) while neuroticism correlated moderately with tense arousal (rs = 0.53; p < 0.05) and hedonic tone (rs = -0.57; p < 0.05). Conclusions: Both personality and vitamin D3 supplementation are related to runners’ pre-run mood. These effects are nullified when it comes to post-run mood states.